Standardisasi Karung Plastik Di Indonesia - Indra Putra; kun Harimurti (Balai Besar Kimia dan Kemasan, 1978)
Standardization of plastic bag in Indonesia covers Standard of Quality and Testing Method. Test of plastic bag with Outer Plastic bag + Inner Liner construction is Carried out with